The Influence of Aerobic Exercise on Intraocular Pressure in Normal Subjects in Late Adolescence - Hasna Fauziyyah; Nur Shani Meida (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2026)
Intraocular pressure (IOP) is an important ocular health parameter and a major modifiable risk factor related to glaucoma. Evidence regarding the acute effect of aerobic exercise on IOP remains inconsistent, particularly in healthy late adolescents. Objective: This study analyzed changes in IOP before and after one session of aerobic exercise. A pre-experimental one-group pretest-posttest design was conducted among 67 university students aged 19-22 years who met the eligibility criteria. Participants performed 20 minutes of jogging at a pace of 6:00-8:00 min/km. IOP in the right eye (OD) and left eye (OS) was measured before exercise and within 2 minutes after exercise using a handheld transpalpebral tonometer. Because the data were not normally distributed, pre-post differences were analyzed using the Wilcoxon signed-rank test. Mean IOP decreased from 17.90 to 15.24 mmHg in OD, representing a mean reduction of 2.66 mmHg. Mean IOP in OS decreased from 18.40 to 15.18 mmHg, representing a mean reduction of 3.22 mmHg. IOP decreased in most participants in OD (48/67) and OS (50/67). The Wilcoxon signed-rank test showed statistically significant pre-post differences in OD (Z = -4.948; p < 0.001; r = 0.604) and OS (Z = -4.945; p < 0.001; r = 0.604). IOP decreased significantly after a single session of aerobic exercise in healthy late adolescents. However, because this study used a one-group design without a control group, the findings should be interpreted as reflecting an acute physiological response rather than evidence of therapeutic efficacy.